2004
DOI: 10.1002/bdrb.20013
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postnatal development studies of lasofoxifene, a selective estrogen receptor modulator (SERM), in Sprague–Dawley rats

Abstract: The maternal findings in this study were related to the pharmacologic activity of lasofoxifene. Inhibition of growth of the F1 offspring after perinatal exposure to lasofoxifene was observed, but there were no significant effects on the sensory, behavioral, or functional measures, including learning and memory. There were no effects on the F2 generation. The findings are consistent with those reported for at least one other SERM. The findings of this study do not suggest increased risk for the primary indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…These observations are consistent with those in another study using a similar treatment period (GD 6-17) in which red vaginal discharge was observed with doses as low 0.1 and 0.03 mg/kg lasofoxifene (Weisenburger et al, 2004). Similarly, presumptive vaginal bleeding between GD 18-20 was reported in rats treated with idoxifene (Treinen et al, 1998) and raloxifene (Buelke-Sam et al, 1998;Byrd and Francis, 1998).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations are consistent with those in another study using a similar treatment period (GD 6-17) in which red vaginal discharge was observed with doses as low 0.1 and 0.03 mg/kg lasofoxifene (Weisenburger et al, 2004). Similarly, presumptive vaginal bleeding between GD 18-20 was reported in rats treated with idoxifene (Treinen et al, 1998) and raloxifene (Buelke-Sam et al, 1998;Byrd and Francis, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, increased systemic levels of somatostatin have been implicated in altered feeding behavior (reviewed in Aponte et al, 1984), altered taste preferences in rats (Scalera and Tarozzi, 1998), and decreased food consumption in rodents and primates (Lotter et al, 1981). Alternate explanations for the lasofoxifene-mediated hypophagy have also been proposed , Terry et al, 2004, Weisenburger et al, 2004. Of note, no clinical signs indicative of frank toxicity were observed in general toxicity studies conducted with similar doses of lasofoxifene (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study support this conclusion and suggest that in some developmental parameters, the lasofoxifene-exposed pups are developmentally 1 week older than controls. Interestingly, no change in age of incisor eruption was reported in the preand post-natal development study with lasofoxifene (Weisenburger et al, 2004). In that study, however, early eye opening was reported and was also interpreted as an artifact of delayed parturition (Weisenburger et al, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…In the implantation study, doses were 0.01, 0.03, and 0.1 mg/kg/day based on findings from two exploratory parturition studies in pregnant rats. The highest dose level in the implantation study was set at 0.1 mg/kg based on pup mortality at a higher doses (Weisenburger et al, 2004). In both the cyclicity and the implantation studies, a constant dose volume of 10 mL/kg was used.…”
Section: Test Article and Treatment Regimenmentioning
confidence: 99%
“…Restoration of normal estrous cycle was achieved one to two weeks after the suspension of therapy 70. As part of an International Conference on Harmonization guideline on reproductive and developmental toxicity testing for new pharmaceuticals [http://www.fda.gov/cder/guidances5a.pdf], a pre- and post-natal study in pregnant and lactating female rats was designed 71. Lasofoxifene at oral doses of 0.01, 0.03, and 1 mg/kg decreased maternal body weight, increased dose-dependently the length of gestation and induced dystocia.…”
Section: Summary Of Pharmacology and Preclinical Evidencementioning
confidence: 99%